Princípios de design educacional e desenvolvimento de recursos educacionais para os cursos técnicos concomitantes EaD do IFRO - Cordenonsi, Adriana Zanki (2022)
The work presented here shows the final results of the research project developed in the Academic Master's Degree in Vocational and Technological Education at the Industrial Technical College of Santa Maria of the Federal University of Santa Maria. The objective of the work was to develop instructional design and educational resources for concomitant vocational courses at the Federal Institute of Rondônia, in order to adapt the teaching-learning process for the teenager target audience, especially regarding the EaD workload present in this modality and which presents deficiencies in its implementation. Initially, a bibliographic survey was carried out on the subject and the theoretical foundations on instructional design, active methodologies, blended learning, educational resources, use of technologies and learning styles were addressed. The investigation with the target audience, in relation to the teaching-learning processes, on the methodologies, resources and media most accepted by this audience, provided subsidies for the development of the design. The methodological foundation is the Design Based Research (DBR), which proposes to identify the problems by those involved in the research and apply the practical and innovative solutions through iterative cycles, in a process of improving the results. Bardin's content analysis was used to verify the results obtained through qualitative and quantitative methods. In addition to the instructional design for the subject, a pedagogical game was developed for content review. The game and the design were applied at the Federal Institute of Rondônia, in the EaD Vocational course in Administration concomitant to high school, in the Marketing discipline. The results showed that students in this age group are eager for more practical classes, use of games and interactivity. The methodologies used in the instructional design project were the flipped classroom and project-based learning, both of which had good acceptance and satisfactory results. The resources developed sought to present various levels of interactivity and were very well accepted. The design principles for this course resulting from the implementation of the instructional design planned for the Marketing discipline were: 1) Diagnosis and Evaluation; 2) Interactivity; 3) Practice; 4) Flipped Classroom.